Chapter Presentazione - Graziani, Michela (Studi di Traduzione Letteraria Lusofona, 2023)
The volume here presented aims to commemorate the Portuguese poet António Correia a year after his death with the translation, for the first time in Italian language, of two collections of sonnets: Deideia and Amagao meu amor, both edited in Macao in 1992. The translation, together with some notes and the essay included in the volume are accompained by personal memories of two Portuguese dear friends of Correia. The volume thus structured aims to introduce the traveling and Eastern Lusitanian soul of António Correia who lived in Macao for almost twenty years. At the same time, the volume aims to present for the first time, through other bio-bibliographical details, the man and the poet António Correia, even now not well known in the Italian and Portuguese academia.